Silence is my Mother Tonque - Addonia, Sulaiman, ....- (London : The Indigo Press, 2023)
Saba arrives in an East African refugee camp as a young girl. In this unfamiliar, crowded and often hostile community, she must carve out a new existence. As she struggles to maintain her sense of self, she remains fiercely protective of her mute brother, Hagos - each sibling resisting the roles gender and society assign.
Keywords: Afrika; Novelle; Oorlog en vrouwen; Vluchtelingenkampen